COMBINED TREATMENT OF RENAL CELL CARCINOMA METASTASIS LOCATED IN THE HUMERUS WITH RECONSTRUCTIVE PLASTIC SURGERY STAGE - S. A. Ivanov; A. A. Klimenko; A. A. Kurilchik; A. L. Starodubtsev; A. D. Kaprin (Исследования и практика в медицине)
In the recent years, the effectiveness of the treatment of even advanced cases of metastatic renal cell carcinoma is relatively high due to the possibility of targeted therapy, removal of metastatic lesions. Therefore, the issue of the quality of life of such patients often comes to the fore. This paper presents a clinical case of radical surgical treatment of metastasis located in the humerus, resulting in partial recovery of the limb function which eventually led to the improvement of the patient’s quality of life.